IMPLEMENTASI CODEIGNITER4 PADA SISTEM PENJUALAN WEB PT. SUPER GRAHA MAKMUR DENGAN PROTOTYPING: IMPLEMENTASI CODEIGNITER4 PADA SISTEM PENJUALAN WEB PT. SUPER GRAHA MAKMUR DENGAN PROTOTYPING - Bagas Aditia; Wendy Asswan Cahyadi; Suhendra Anjar Dinata (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
PT. Super Graha Makmur is one of the companies engaged in the field of Furniture, PT. Super Graha Makmur is growing and continues to strive to improve the services and quality standards of the company from various sides, PT. Super Graha Makmur wants its business to be able to grow in using one of the customer-oriented business strategies. In the company, the current online sales system can only be found in several marketplaces so it is less effective, so it is a shame if you do not have your own website-based sales system, besides that there are several policies that must be followed if you want to sell in the marketplace, and also the company will experience difficulties because of the limited process of disbursing money from sales because they have to wait for orders to be received by customers and it will take quite a long time.